Dietary Patterns and Physical Activity Associated with Acute Respiratory Infection Primary Care Patients in East Halmahera, Indonesia: A Cross-Sectional Study - Youdy Wellem Kalumata; Yuni Asri; Ananda Sagita Maharani (Journal of Educational Innovation and Public Health, 2026)
Background: Acute respiratory infection (ARI) remains a major public health concern, particularly in primary care settings. Lifestyle factors such as dietary patterns and physical activity are increasingly recognized as potential contributors to respiratory health. Objective: This study aimed to examine the association between dietary patterns, physical activity, and ARI among primary care patients in East Halmahera, Indonesia. Methods: A cross-sectional study was conducted at a primary health care facility in East Halmahera, Indonesia, from January to February 2026, involving 106 respondents selected using a total sampling technique. Data were collected using structured questionnaires and medical records. Variables included sociodemographic characteristics, dietary patterns, physical activity, and ARI status. Data were analyzed using descriptive statistics and Chi-square tests with a significance level of p < 0.05. Results: The prevalence of ARI among respondents was 77.4%. Bivariate analysis showed that dietary patterns (p = 0.006) and physical activity (p = 0.015) were significantly associated with ARI. In contrast, age, gender, marital status, education level, employment status, smoking, and alcohol consumption were not significantly associated with ARI (p > 0.05). Conclusion: Dietary patterns and physical activity were significantly associated with ARI among primary care patients in East Halmahera. These findings highlight the importance of lifestyle-related factors in addressing respiratory infections at the primary care level.